Institutional experience of the multimodality treatment of cancer tongue - Shankar, Mrinal; Pattanayak, Manisa; Nautiyal, Vipul; Saini, Sunil (International Surgery Journal, 2017)
Background: Cancer (Ca) tongue incidence has shown a rising trend in India in the last couple of years. Increasing use of tobacco being the main risk factor. Guidelines available for management of this disease include it broadly under oral cavity cancers. However, the biological behaviour of this disease is warrant of more aggressive approach to treatment. In early stage disease, treatment is mainly with single modality, surgery being the most preferred. Locally advanced disease treated with multimodality approach with surgery and adjuvant RT/chemoRT. Adverse histopathological factors are important prognostic indicators for early recurrence. Even if the mainstay of treatment in metastatic disease is palliation, multimodality approach is preferred. The aim of the study is to study clinical profile of Ca tongue ant to study outcome of multimodality management of SCC tongue and identification of treatment failure. Methods: The study was conducted in the Department of Surgery, Himalayan Institute of Medical Sciences, Dehradun, Uttarakhand, India over a period of 12 months on patients attending Surgical Oncology OPD. Written informed consent and ethical committee clearance was obtained in all 64 cases included, and study type is observational. Results: This is an observational study conducted at Himalayan Institute of Medical Sciences, Dehradun over a period of 12 months. 64 patients diagnosed with SCC tongue were included. Treatment protocols were prescribed by the multidisciplinary tumour board, and patients were followed up to 6 months after completion of the planned treatment. 68.75% patients were below 55 years of age. 87.5% were chronic tobacco chewers. 79.68% had lesion in the anterior tongue. 84.37% received treatment with curative intent (of these 16.66% patients showed early recurrence). 71.86% patients underwent definitive surgery (of these 78.26% remained disease free after 6 months of completion of treatment). Radiotherapy was used in both adjuvant and primary setting. Nodal recurrence was the commonest pattern of recurrence in patients who had underwent definitive surgery. Co-relation with adverse histopathological prognostic indicators also establish early recurrence. Conclusions: Ca tongue was found to be commoner in individuals between 36-55 years. Tobacco users were seen to be at high risk. Surgery was the preferred modality of treatment in early stage disease. Regional lymph node metastasis is the commonest site of early treatment failure. Adverse histopathological factors were important indicators of prognosis and need consideration in planning adjuvant treatment.